Plasma symmetric dimethylarginine as a metabolite biomarker of severe acute ischemic stroke - Pihlasviita, Saana; Mattila, Olli S.; Nukarinen, Tiina; Kuisma, Markku; Harve-Rytsälä, Heini; Ritvonen, Juhani; Sibolt, Gerli; Curtze, Sami; Strbian, Daniel; Pystynen, Mikko; Tatlisumak, Turgut; Lindsberg, Perttu J. (Frontiers in Neurology, 2024)
IntroductionAfter severe ischemic stroke (IS), circulating levels of symmetric dimethylarginine (SDMA) increase. We investigated the early dynamics of SDMA in stroke to potentially aid with prehospital identification of severe IS from hemorrhagic stroke (HS).MethodsWe performed targeted mass spectrometry (MS) measurements of SDMA in two sequential acute plasma samples (early and secondary) of 50 IS patients with LVO and 49 HS patients. Secondary samples of 227 IS and 84 HS patients with moderate to severe symptoms (NIHSS ≥ 7) subsequently underwent ELISA validation.ResultsThe median (IQR) last-known-well (LKW) to sampling times were 43 min (35–67) for early samples in the MS analysis, and 83 min (65–113) for secondary samples in MS and ELISA analyses. No inter-group differences existed in early samples, but IS patients had significantly higher mean (IQR) SDMA levels in secondary samples in both analyses: 5.8 (5.3–6.9) vs. 5.1 (4.2–5.8) A.U. for HS, p < 0.001, with MS; and 0.82 (0.72–1.01) vs. 0.71 (0.58–0.85) nmol/mL for HS, p < 0.001, with ELISA. For IS patients, higher SDMA levels were associated with cardioembolic stroke: 0.84 (0.73–1.09) vs. 0.79 (0.71–0.91) nmol/mL for other etiologies, p = 0.042, and poor outcome: modified Rankin Scale (mRS) 4–6; 0.90 (0.73–1.06) vs. 0.80 (0.72–0.97) nmol/mL for mRS 0–3 (p = 0.045).ConclusionIn a large clinical cohort of stroke patients with moderate to severe symptoms, our data suggest that SDMA can assist in differentiation of IS and HS patients already 1 h and a half after symptom onset. SDMA may prove to have future value in a diagnostic stroke biomarker panel.